(untitled) (Rasividya : Jurnal Pendidikan, 2025)
In this article, we will discuss education in Banggai Regency, especially SD Inpres Bukit Makarti. Deviant behavior and attitudes can be found in schools. For example, not complying with school rules, especially violations or deviations from social and religious norms; disobedience to educators; bullying schoolmates; disobeying government regulations; even at home, often against parents, dishonest; and so on. At SD Inpres Bukit Makarti, religious and moral learning is based on the principles of religion and character. This paper will discuss what Chess Teachers learned about the formation of students’ character as one of the religious teachings used in the character formation process